Young women's recent experience of labour and birth care in Queensland. - Redshaw, M; Hennegan, J; Miller, Y (2014)
BACKGROUND: young parenthood continues to be an issue of concern in terms of clinical and psychosocial outcomes for mothers and their babies, with higher rates of medical complications such as preterm labour and hypertensive disease and a higher risk of depression. The aim of this study was to investigate how young age impacts on women's experience of intrapartum care. METHODS: secondary analysis of data collected in a population based survey of women who had recently given birth in Queensland, comparing clinical and interpersonal aspects of the intrapartum maternity care experience for 237 eligible women aged 15-20 years and 6534 aged more than 20 years. Descriptive and multivariate analyses were undertaken. RESULTS: in the univariate analysis a number of variables were significantly associated with clinical aspects of labour and birth and perceptions of care: young women were more likely to birth in a public facility, to travel for birth and to live in less economically advantaged areas, to have a normal vaginal birth and to have one carer through labour. They were also less likely to report being treated with respect and kindness and talked to in a way they could understand. In logistic regression models, after adjustment for parity, other socio-demographic factors and mode of birth, younger mothers were still more likely to birth in a public facility, to travel for birth, to be more critical about interpersonal and aspects of care and the hospital or birth centre environment. CONCLUSION: this study shows how experience of care during labour and birth is different for young women. Young women reported poorer quality interpersonal care which may well reflect an inferior care experience and stereotyping by health professionals, indicating a need for more effective staff engagement with young women at this time.